PENGARUH KEMITRAAN DAN VARIABEL LAINNYA TERHADAP KEUNTUNGAN UMK INDUSTRI MAKANAN DI INDONESIA - Fauziah, Syifa; Rifin, Amzul; Adhi, Andriyono Kilat (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
Food industry contributes a high good of labor absorption dominates in the manufacturing sector or the contribution to the total national GDP. The industry is in fact in domination by the perpetrators of Micro small and medium enterprises (MSMEs). The objectives of this research is to know the impact of partnerships and other variables against the profit of micro and small enterprises of the food industry. Multiple regression method is used to see what variables affect the profit of micro and small enterprises of the food industry entrepreneur. The results showed that dummy variables such as length of business, partnerships, education level, number of labor, the cost, the number of working hours per day, the age of the entrepreneur and the dummy sectors of the food industry influence on the profit of micro and small enterprises in the food industry. The amount of the issued capital property does not affect the profit the venture. The actors who do venture partnership is still very slightly so that the policy to encourage and develop business partnerships between the various patterns of cooperatives, small medium enterprises and large scale effort undertaken is just right and should be noted in order to sustainable.